Sorghum Corpoica JJT-18 silage production as a business model in Colombia - Gallo Caro, Irieleth; Enciso, Karen; Sotelo Cabrera, Mauricio Efren; Burkart, Stefan (International Center for Tropical Agriculture, 2021)
Climate variability phenomena such as intense droughts greatly affect the cattle sector in the Colombian Orinoquía region. One strategy for solving this problem is silage. Silage production as a business model is an economically and financially viable practice, thus allowing cattle and forage producers to obtain additional income. Sorghum Corpoica JJT-18 is a promising variety for cattle feed in the Orinoquía region since its agronomic performance and high quality are superior to those of the crops commonly used for animal feeding in the region.